PELATIHAN KEWIRAUSAHAAN DIGITAL UNTUK PENGEMBANGAN UMKM DAN MAHASISWA DI KOTA BENGKULU - Desriani, Neny; Wahyudi, Heru (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Fourth Industrial Revolution has transformed the global business landscape with digital technologies like the Internet of Things (IoT), Artificial Intelligence (AI), and big data, presenting challenges and opportunities for entrepreneurs, especially Micro, Small, and Medium Enterprises (MSMEs) and students in Bengkulu City. This community service program aimed to address the digitalization knowledge and skills gap among these groups by enhancing their understanding of digital entrepreneurship, developing practical digital marketing skills, and supporting MSMEs' digital transformation. The training covered six main topics: understanding entrepreneurship, contemporary entrepreneurial challenges, digital technology adoption, basics of digital media (email and Google Business), basics of digital media (social media), and introduction to Online Single Submission (OSS) for business legality. Evaluation results showed a significant increase in participants' knowledge and skills in digital marketing, social media management, and technology adoption, with most participants reporting substantial benefits and improved readiness to start and manage their businesses digitally. The program not only provided immediate benefits to the participants but also contributed to MSME development in Bengkulu City by offering a training model adaptable for future initiatives, aiming to enhance MSMEs' digital capacity and prepare students for entrepreneurial ventures.